Grow With the Challenge – Microbial Effects on Epithelial Proliferation, Carcinogenesis, and Cancer Therapy - von Frieling, Jakob; Fink, Christine; Hamm, Jacob; Klischies, Kenneth; Forster, Michael; Bosch, Thomas C. G.; Roeder, Thomas; Rosenstiel, Philip; Sommer, Felix (Frontiers in Microbiology, 2018)
The eukaryotic host is in close contact to myriads of resident and transient microbes, which influence crucial physiological pathways. Emerging evidence points to a role of host-microbe interactions for controlling tissue homeostasis, cell fate decisions and regenerative capacity in epithelial barrier organs including the skin, lung and gut. In humans and mice, it has been shown that malignant tumors of these organs harbor an altered microbiota. Mechanistic studies have shown that altered metabolic properties and secreted factors contribute to epithelial carcinogenesis and tumor progression. Exciting recent work points towards a crucial influence of the associated microbial communities on the response to chemotherapy and immune-check point inhibitors during cancer treatment, which suggests that modulation of the microbiota might be a powerful tool for personalized oncology. In this article, we provide an overview of how bacterial signals and signatures may influence epithelial homeostasis across taxa from cnidarians to vertebrates and delineate mechanisms, which might be potential targets for therapy of human diseases by either harnessing barrier integrity (infection and inflammation) or restoring uncontrolled proliferation (cancer).